Reasons for Delaying Marriage By Japanese Women and its Impact and the Shoushika Phenomenon in the Japan Reporter Youtube Channel: Japan's Rise of Unmarried and Childless Women | Birthrate Crisis (EP.4) - Widhiutami, Bintang Satyaningwulan; Santoso, Budi (Borong Newinera Publisher, 2025)
This study aims to analyze the causes and effects of marriage delay by Japanese women on the shoushika (low birthrate society) phenomenon as depicted in The Japan Reporter's YouTube video: